2005
DOI: 10.1021/jm050362n
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Assessment of Docking Programs and Scoring Functions

Abstract: Docking is a computational technique that samples conformations of small molecules in protein binding sites; scoring functions are used to assess which of these conformations best complements the protein binding site. An evaluation of 10 docking programs and 37 scoring functions was conducted against eight proteins of seven protein types for three tasks: binding mode prediction, virtual screening for lead identification, and rank-ordering by affinity for lead optimization. All of the docking programs were able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
1,519
6
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,471 publications
(1,582 citation statements)
references
References 50 publications
49
1,519
6
8
Order By: Relevance
“…The present assessment of the accuracy of AutoDock for protein-ligand docking concurs with earlier results, 15 in that, the predicted binding configurations are generally quite close to the target configurations but the binding energies are not very reliable. Thus AutoDock predictions for the binding positions can be profitably used as initial configurations in MD simulations, with the provision that the ligand does not come into contact with the peptide (cf.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The present assessment of the accuracy of AutoDock for protein-ligand docking concurs with earlier results, 15 in that, the predicted binding configurations are generally quite close to the target configurations but the binding energies are not very reliable. Thus AutoDock predictions for the binding positions can be profitably used as initial configurations in MD simulations, with the provision that the ligand does not come into contact with the peptide (cf.…”
Section: Resultssupporting
confidence: 85%
“…14 For example, a recent test of various docking programs revealed that none of them could reliably predict the ligand binding affinities. 15 On the positive side, docking predictions for the binding configurations were not too far from the experimentally determined bound complex structures, 15 giving hope that docking methods may provide useful starting configurations for MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Some programs have been reported to be more suitable for some protein systems than other proteins. 1 Understanding the performance of LibDock for a particular protein system may provide information on how best to use the algorithm in the future.…”
Section: Resultsmentioning
confidence: 99%
“…The recently reported GSK docking-scoring study 1 included two programs, MVP 12 and Fred, 20 which used binding site information in their docking-scoring algorithms. The first program, MVP, used atom-type target points to superimpose ligands in the binding site and performed well in both docking accuracy and retrieval of actives in a virtual screening.…”
Section: Introductionmentioning
confidence: 99%
“…Much work needs to be done to improve the scoring functions towards a direct estimation of free energies of binding (see structure-based methodologies section). However, docking programs have demonstrated a substantial reliability in the prediction of ligand binding modes and bioactive conformations [83]. Dealing with crystal structures of nuclear hormone receptors and enzymes, Sippl amply demonstrated the advantages of combining the accuracy of ligand alignments obtained through docking with the computational efficiency of 3D-QSAR methodologies [84][85][86][87].…”
Section: Combining Ligand and Structure-based Methodsologiesmentioning
confidence: 99%